Agricultural water conservation in China: plastic mulch and traditional irrigation. Issue 4 (11th June 2015) - Ingman, Mark; Santelmann, Mary V.; Tilt, Bryan
Abstract : Plastic mulch is commonly used with micro‐irrigation in developed countries; however, Chinese farmers use plastic mulch on a vast scale independent of micro‐irrigation. For the past three decades, China's land area in plastic mulch has exceeded the world's total land area in micro‐irrigation. We report results from the water‐scarce region of Minqin County, where 87% of Chinese farmers interviewed responded that they use plastic mulch to conserve water and 53% to increase yields. Survey results indicated the desire to conserve water through the use of plastic mulch to be statistically equivalent to the desire to increase yields. Responses to interviews and surveys indicate that farmers perceive water savings of 24–26% when plastic mulch is used. Interview and survey responses suggest farming families are shifting to purchasing wheat from outside the region; a potential import of "virtual water" into this water‐scarce region.